Catalysis in biodiesel synthesis: challenges and future perspectives - Fauzi, A. H. M. (Springer US, 2013)
The necessity to search for fossil fuel alternative is getting more critical with the increasing fossil fuel price and also its limited supply. The use of mineral diesel for transport sector is unfeasible as it is nonrenewable and emits greenhouse gases to the atmosphere during combustion, particularly carbon dioxide which can lead to global warming phenomena. Biodiesel is a type of biofuel that can be produced using renewable resources such as biomass. It can be produced from oils and fats through transesterification process. The presence of catalyst is important to ensure that the reaction can progress at shorter time and produce high biodiesel yield. Numerous catalysts have been used to assist the transesterification process. They include homogeneous and heterogeneous catalysts and can be further divided into acid and base nature. The catalysis in biodiesel production is progressing at faster rate in order to find a catalyst that is more practical for larger production scale. Ionic liquids and ionic solids are among new catalysts introduced with aim to improve the efficiency of the process. This chapter focused on the benefits and drawbacks of different catalysts for biodiesel synthesis. The applications of novel processes for more sustainable and enhanced biodiesel production are also discussed.